A Business Processes Reference Model for Course Document Management for Supporting Accreditation - Alshish, Mohammed G. S. Ali (2010)
A reference model is a fundamental starting point for the development of new information systems. Reference models are also called universal models, generic models, or model patterns. In order to obtain a higher learning programme accreditation, most of the educational institutions such as private and public universities have to clearly demonstrate that the programmes offered by them meet the quality standards established by the accreditation body. However, there is no complete and effective reference model for the business process of managing courses' document in order to support accreditation. Therefore, this master's thesis is an attempting to design a reference model, which will be as a general reference model for the business processes of managing document of courses in higher educational institutions and universities in order to obtain accreditation. As the processes to obtain the accreditation is almost similar in most universities and higher educational institutions around world, this study tries to design general business processes reference model to these process that can be as a reference for any education institutions to model its own model since the specific model is a partial model of the reference model. Moreover based on this reference model, the requirements model for Universiti Utara Malaysia (UUM)was designed and implemented as web-based system for Courses' document management supporting Accreditation. In addition to this, the purposed reference model covers all processes that are used in most universities and higher educational institutions to store, retrieve and organise the information of the courses. The methodology of this study is the general design research methodology that contained; awareness of problem, suggestion, development, evaluation, and conclusion. To evaluate the system that was designed and implemented based on the reference model, two methods was used. The first one is black box testing to ensure that the functionality specified in the requirement specification works. The other method is the questionnaire to evaluate the usability of the systems in terms of usefulness. The summary of evaluation results emphasises that this system provides an enhancement and improvement to the performance of the users to accomplish their tasks, and enables the users to complete their tasks quickly.